STUDI POTENSI TERBENTUKNYA CEBAKAN MINERAL RADIOAKTIF PADA BATUAN GRANITIK DI PULAU SULAWESI: THE STUDY ON THE POTENTIAL OF RADIOACTIVE MINERAL DEPOSITS FORMATION IN GRANITIC ROCKS IN SULAWESI ISLAND - Ngadenin; Widodo; Fauzi, Rachman; Pratiwi, Fadiah (Buletin Sumber Daya Geologi, 2021)
In the Island of Sulawesi, there are many granitic rocks which have potential for containing radioactive mineral deposits. The purpose of this study is to determine the type of radioactive mineral deposits based on radioactivity, uranium grade, and mineralogy characteristics of certain granitic rocks. The data used comprise radioactivity measurement, uranium content, megascopic and petrographic observations of rocks, and grain analysis of heavy mineral of granitic rocks from uranium exploration on the island of Sulawesi. The granitic rocks consist of granite, biotite granite, granodiorite, biotite granodiorite, hornblenda granodiorite, hornblenda biotite granodiorite, biotite hornblenda granodiorite, biotite adamelite, hornblenda biotite adamelite, biotite hornblenda diorite, diorite, biotite hornblenda diorite and syenite. The radioactivity of granitic rocks is 50 to 1,200 c/s and uranium content is 0.54 to 36 ppm. Radioactive minerals found in granitic rocks consist of zircon, monazite, alanite, thorite, and branerite. The potential occurrence of radioactive mineral deposits on the island of Sulawesi are placer-type thorium deposits at the modern deltas and coasts.